Morfologi, Anatomi dan Taksonomi Bambusa vulgaris Koleksi Kebun Raya Bogor - Nikmah Musa; Y. C. Sulistyaningsih; Elizabeth A. Widjaja (PTTI, 1997)
Morphology, Anatomy and taxonomy of Bogor Botanical gardens collection of Bambusa vulgaris